Efektivitas Sistem Seedtrack Berbasis Blockchain Dalam Tata Kelola Lingkungan Hutan Rakyat - Ramadhan, Dede; Ahleyani, M. (JURNAL NAWALA POLITIKA, 2025)
The use of digital technology in the forestry sector is an urgent need to address the challenges of transparency, accountability, and sustainability. Forest seed certification and tracking still face various problems, such as certificate forgery, illegal distribution, and weak public trust in conventional systems. This research developed SEEDTRACK, a blockchain-based digital integration system supported by new and renewable energy (EBT), to produce a transparent, secure, and sustainable seed certification and tracking solution. The research method used a Research and Development (R&D) approach with mixed methods, including literature studies, interviews, FGDs, blockchain architecture design, EBT integration, prototype development, and field trials. The results showed that SEEDTRACK was able to increase seed tracking accuracy by 28%, accelerate the certification process by 35%, and reduce the risk of data manipulation by 40% compared to manual systems. In addition, the EBT integration resulted in 22% higher energy efficiency compared to the conventional system baseline. This system is relevant to achieving the 2030 SDGs, particularly goals 7 (Affordable and Clean Energy), 13 (Addressing Climate Change), and 15 (Conserving Terrestrial Ecosystems). Therefore, SEEDTRACK has the potential to become a national model for forest seed management that can be replicated across other natural resource sectors.